Implementasi Prinsip Muamalah dan Infrastruktur Pasar terhadap Keputusan Pembelian Produk Halal - Eva Ruliana (Dinar Islamic Review, 2020)
This study aims to determine the effect of implementing the principles of muamalah and infrastructure on purchasing decisions for halal products in the Kota Agung sub-district market, Tanggamus district. The research method used is quantitative research. The respondent's data collection technique used a questionnaire which was distributed to the public directly. Interviews with several respondents were also conducted. A sample of 100 respondents was taken using the Slovin formula and then analyzed using multiple linear regression analysis using purposive sampling technique. The results of the Ftest test show that the two independent variables simultaneously have a positive and significant effect of 27.4% on the decision to purchase halal products at the Kota Agung Tanggamus market and the remaining 72.6% are influenced by other variables outside this model. The findings also reveal that the principle of muamalah is still not able to strongly encourage purchasing decisions for halal products in traditional markets. This can be seen from the R value which is only 52.4%. Infrastructure is also still felt that needs to be addressed so that people are more comfortable shopping at the people's market. Apparently, other factors should be investigated for the future.